Pediatric Thyroidectomy: Hospital Course and Perioperative Complications. (20th December 2016) - Hanba, Curtis; Svider, Peter F.; Siegel, Bianca; Sheyn, Anthony; Shkoukani, Mahdi; Lin, Ho‐Sheng; Raza, S. Naweed
Abstract : Objectives/Hypothesis: To evaluate hospital course and associated complications among pediatric patients undergoing thyroidectomy. Study Design and Setting: Retrospective database review of the Kids' Inpatient Database (2009, 2012). Methods: The Kids' Inpatient Database was evaluated for thyroidectomy patients for the years 2009 and 2012. Surgical procedure, patient demographics, length of stay, hospital charges (in US dollars), and surgical complications were evaluated. Results: Of an estimated 1099 nationwide partial thyroidectomies and 1654 total thyroidectomies, females accounted for 73.5% and 79.1% of patients, respectively. Children <1 year of age had significantly longer hospital courses ( P <. 0001), and patients 1 to 5 years of age had a significantly greater length of stay than individuals 6 to 20 years of age (7.8 vs 2.1 days, P <. 001). The most common complications overall included hypocalcemia, respiratory complications, vocal cord paresis/paralysis, postoperative infection, and bleeding. Vocal cord paralysis was noted in 1.7% of pediatric thyroidectomy patients. The presence of these complications among total thyroidectomy patients significantly increased one's length of stay and hospital charges. A neck dissection was reported in 22.9% of malignant thyroidectomy patients. Conclusion: Nearly 20% of children who underwent total thyroidectomy experienced postoperative hypocalcemia, positing a need for the development of postoperative calcium replacement algorithms to minimize the sequelae of hypocalcemia. A greater incidence of respiratory and infectious complications among younger patients (<6 years) suggests a need for closer monitoring, possibly encompassing routine postoperative intensive care unit utilization, in an attempt to minimize these sequelae.